Calcipenic Rickets Accompanied by Hypercoagulability, Hypokalemia and a History of Secondary Amenorrhea: A Case Report - Radiyati Umi Partan; Merylla Filianty Sipayung; Ratna Maila Dewi (HM Publisher, 2023)
mineralization. This case report aims to present a patient with calcipenic rickets, which are accompanied by hypercoagulability, hypokalemia, and secondary amenorrhea. In this case, a woman, 21 years old, unmarried, living outside the city of Palembang, came to the endocrine polyclinic with complaints of leg pain, making it difficult to walk along with growth retardation. In addition, there is a lump on the right arm and left knee that does not enlarge, height and weight do not increase, and both legs are bent. Based on physical examination, the general condition looked moderately ill, with vital signs within normal limits, body weight 26 kg, height 123 cm, and body mass index 17.8 kg/cm2. In the superior extremity, a 2-3 cm mass was found in the right humerus. In the lower extremities, there was a mass measuring 3 cm in the left lateral genu, supple and easy to move, with no pain. On examination of genital maturity, Tanner 2 was found. Laboratory evaluation results at the first visit to the endocrine clinic showed increased fibrinogen, d-dimer level, parathyroid hormone, and alkaline phosphatase. In addition, there was a decrease in calcium, potassium, vitamin D-25 OH, phosphorus, growth hormone, and anti-Mullerian hormone. Bone age examination shows bone age according to girls aged 15 years. The patient was diagnosed with calcigenic type rickets with hypercoagulability, hypokalemia, and secondary amenorrhea. Initial management is given calcium 500-4000 g/day, potassium 40-100 mEq/24 hours, warfarin 2 mg/24 hours, acetylsalicylic acid 80 mg/24 hours, vitamin D 1000 mg/24 hours, CaCO3 500 mg/8 hours, potassium chloride 600 mg/12 hours. In conclusion, cases of rickets are quite rare and require further examination to establish a diagnosis.